2017
DOI: 10.1387/ijdb.160006sb
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid assisted reprogramming of fibroblasts for generation of pluripotent stem cells in buffalo (Bubalus bubalis)

Abstract: Generation of pluripotent stem cells by reprogramming somatic cells of quality animals has numerous potential applications in agricultural and biomedical sciences. Unfortunately, till now, reprogramming of buffalo fetal fibroblast cells (bFFs) has been very ineffient despite intensive efforts. Here, we attempted to enhance reprogramming efficiency by using the HDAC inhibitor valproic acid (VPA) in bFFs transfected with pLentG-KOSM pseudo virus carrying mouse specific pluripotent genes. FACS analysis revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Analogous methods of HDACiand/or DNMTi-dependent epigenetic transformation have been adapted to enhance capabilities of parental genomes to be epigenetically reprogrammed in the in vitro fertilization (IVF)-derived embryos [17][18][19][20]. Such approaches have also been used either to expedite the epigenomic reprogramming and molecular dedifferentiation of adult somatic cells or mesenchymal stem cells (MSCs) into induced pluripotent stem cells (iPSCs) [21][22][23][24][25] or to facilitate the molecular rejuvenation of adult MSCs [21,26,27]. Moreover, the efforts that are aimed at the epigenomic modulation dependent on HDACi and/or DNMTi approved by the U.S. Food and Drug Administration (FDA) or by European Medicines Agency (EMA) have been undertaken to accomplish clinical treatments (i.e., epigenetic therapies) in oncologic patients and medical patients afflicted by neurodegenerative diseases or psychiatric disorders [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Analogous methods of HDACiand/or DNMTi-dependent epigenetic transformation have been adapted to enhance capabilities of parental genomes to be epigenetically reprogrammed in the in vitro fertilization (IVF)-derived embryos [17][18][19][20]. Such approaches have also been used either to expedite the epigenomic reprogramming and molecular dedifferentiation of adult somatic cells or mesenchymal stem cells (MSCs) into induced pluripotent stem cells (iPSCs) [21][22][23][24][25] or to facilitate the molecular rejuvenation of adult MSCs [21,26,27]. Moreover, the efforts that are aimed at the epigenomic modulation dependent on HDACi and/or DNMTi approved by the U.S. Food and Drug Administration (FDA) or by European Medicines Agency (EMA) have been undertaken to accomplish clinical treatments (i.e., epigenetic therapies) in oncologic patients and medical patients afflicted by neurodegenerative diseases or psychiatric disorders [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…After seeding, the colonies were attached and spread eventually in control and CNT scaffolds with compact roundness like morphology of pluripotent stem cells (Fig 1C). The compact round morphology of typical iPSC colonies were maintained on all the surfaces even after 72 hours of incubation (Fig 2D ) The pluripotency of iPSC is defined in terms that whether the cells have the capability to differentiate into three germ layers in vitro or in vivo (Mahapatra et al, 2016). ciPSC are unique in their ability to express pluripotency markers and higher ALP activity (Baird et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that even at low doses, the histone deacetylase inhibitor TSA was able to stabilize expression of pluripotent genes. Similarly, VPA was found to stabilize histone acetylation and the expression of pluripotent gene in bovine iPS cells (Mahapatra et al 2015). It was also shown that the use of such chemicals to increase reprogramming efficiency could also replace one or more of the key factors found to induce reprogramming (Ma et al 2017).…”
Section: Dnamentioning
confidence: 96%